2023
DOI: 10.58811/opsearch.v2i2.40
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Combretum nigricans Hot Aqueous Extracts on Phenylhadrazine- Induced Hemolytic Anaemia in Wistar Rats

J.G. Nangbes

Abstract: Anaemia is a major health issue that affects many people, particularly in developing nations. In some cases of anemia, rural residents in the tropics have to rely on traditional remedies. The goal of this study was to determine Combretum nigricans’s hematinic capabilities. Using phenylhydrazine (PHZ)-induced anemia in rats, the aqueous extract (AE) of the bark was tested for haematinic effects. A total of twenty-eight (28) wistar albino rats of both sexes, weighing between 150 – 250g, were used for the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Previous studies reported anticancer properties with triterpenes extracted from the leaf methanolic extract [ 18 ] and anthelminthic activities with the organic and aqueous extracts of fruits against the levamisole-resistant strain of Caenorhabditis elegans [ 19 ]. Other investigations found antimalarial [ 20 ], antianemia [ 21 ], and antifungal [ 22 ] activities. However, little information is available on their filaricidal activities, yet a recent ethnobotanical study showed that the populations of Far North Cameroon use Combretum species to treat onchocerciasis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported anticancer properties with triterpenes extracted from the leaf methanolic extract [ 18 ] and anthelminthic activities with the organic and aqueous extracts of fruits against the levamisole-resistant strain of Caenorhabditis elegans [ 19 ]. Other investigations found antimalarial [ 20 ], antianemia [ 21 ], and antifungal [ 22 ] activities. However, little information is available on their filaricidal activities, yet a recent ethnobotanical study showed that the populations of Far North Cameroon use Combretum species to treat onchocerciasis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%